The Concept of Patience in Islam and Its Implications for Education - Solihin, Arip; Supriadi, Udin; Suresman, Edi (TARBAWY: Indonesian Journal of Islamic Education, 2022)
Abstract Patience is very important in everyday life, both in school education (formal) and education in the family. Patience requires certain mental processes and attitudes that are effective if taught in the family. Indonesian people use the concept of ‘patient’ very much, both in religious and cultural contexts. In everyday life, this concept is also widely used by people when facing various psychological problems, for example dealing with stressful situations, facing problems, disasters or when getting angry. The qur’an commands believers to adorn themselves with patience, because patience has great benefits in educating oneself, strengthening personality, increasing human ability to endure difficulties and face various problems and burdens of life.Abstrak Kesabaran sangat penting dalam kehidupan sehari-hari, baik dalam pendidikan sekolah (formal) maupun pendidikan dalam keluarga. Kesabaran membutuhkan proses mental dan sikap tertentu yang efektif jika diajarkan dalam keluarga. Orang Indonesia sangat banyak menggunakan konsep ‘sabar’, baik dalam konteks agama maupun budaya. Dalam kehidupan sehari-hari, konsep ini juga banyak digunakan orang saat menghadapi berbagai masalah psikologis, misalnya saat menghadapi situasi stres, menghadapi masalah, bencana atau saat mengalami kondisi marah. Al-Qur’an memerintahkan orang beriman untuk menghiasi dirinya dengan kesabaran, karena kesabaran memiliki manfaat yang besar dalam mendidik diri, memperkokoh kepribadian, meningkatkan kemampuan manusia dalam menghadapi kesulitan dan menghadapi berbagai persoalan dan beban hidup.